TEOLOGI KRISTEN DAN ETIKA PERGAULAN SEBAGAI FONDASI ALKITABIAH DALAM MEMBANGUN INTERAKSI SOSIAL YANG BAIK - Ines Astrid; Fera Monika, Salotina Nabyal, Enggel Pahabol, Aris Seno (ADISAM PUBLISHER, 2025)
Social ethics from a Christian theological perspective has an important role in shaping character and social interactions in accordance with Biblical values. This article discusses the concept of social ethics in the light of Christian theology, with a focus on the teachings of Jesus Christ and the views of the Apostles. Through theological studies, good social ethics involves love, truth, loyalty and respect for others. In the context of the digital era, the challenges in implementing social ethics are increasingly complex, requiring a deep understanding of Christian principles in building healthy and meaningful relationships